Penentuan Prioritas Penyewaan Armada Angkutan Crude Palm Oil (CPO) Berbasis Multi Platform Menggunakan Algoritma Electre - Ardyansah, Ardyansah; Herlinah, Herlinah; Billy Eden William Asrul (Prosiding SISFOTEK, 2023)
CV. ABN Transport is a company providing Crude Palm Oil (CPO) transportation fleets in East Kalimantan with a fleet of seven (7) units, capable of transporting 8 tons of CPO liquid. This research aims to design a multi-platform based application that utilizes the ELECTRE algorithm to determine fleet rental priorities and the Google Maps API to obtain rental origin and destination locations and calculate mileage. The main objective is to overcome delivery schedule problems that often occur and ensure the effectiveness and efficiency of utilizing the rented fleet. This research uses the ELECTRE method to rank tank truck fleet rental priorities by collecting data through observation, interviews and literature study. The research design uses Unified Modeling Language (UML) functional modeling, including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. In the application, the RESTful API architecture is used in the Laravel framework to enable easy and effective API creation and management. On the mobile side, a Model View Controller (MVC) is used in the Flutter framework and the database is implemented with MySQL. Based on the results of application testing, 8 respondents as a sample, 50% of users agreed that the application provides rental order recommendations based on the weight of the assessment criteria and helps in making prioritization decisions. Apart from that, 33.33% of respondents strongly agreed and 16.67% somewhat agreed with the statement. In conclusion, the application designed can assist CV ABN transport to determine CPO fleet rental prioritas more affectively and efficiently due to the use of the ELECTRE Algoritm and Google Maps API integraton to manage the rental of pick up location and destination.